Funkcje sankcji prawnych w prawie administracyjnym – zagadnienia wybrane - Lewicki, Marek (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The issue of the function of legal sanctions in the administration law is complex. It results, among others, from the possibility to understand the term “a legal sanction” in different ways. This term can be defined as a particular rule or provision, the act of application thereof, or the outcome of its execution. In practice, the issue of subject, which determines the function of particular sanctions, is also extremely significant. It can be generally said that legal sanctions in administration law can perform five functions: preventive, repressive, compelling, restrictive and redistributive.